The Tariff Liberalisation Policy Nexus with Non-Tariff Measures: Panel Model Evidence in the SA–EU Fruit Products Trade - Chiedza L. Muchopa (Economies)
Higher levels of quota granted can induce and increase exports, but the impact is not the same across all tariff lines. Answers are sought to the question of how the level of exports changes as the quota size of tariff rate quotas changes, thus enabling the investigation of whether unilateral quotas granted to South Africa by the European Union have influenced fruit products’ export flows in the presence of non-tariff measures. Drawing on panel data regression techniques, this study observes five fruit products’ tariff rate quotas repeatedly from 2004 to 2021. It also incorporates a variable to capture non-tariff measures based on the data from the WTO I-TIP database. The findings indicate a positive relationship between quota size and exports, further showing that for a given quota size, the increase in exports is small in the presence of non-tariff measures. These findings draw attention to future trade reforms that focus on seeking the expansion of quota size for the most productive tariff lines in terms of export growth while aiming for the simultaneous reduction of non-tariff measures and tariff rates.